Pengaruh Ekstrak Etanol Bonggol Musa paradisiaca var. balbisiana Colla terhadap Diameter Zona Hambat Staphylococcus aureus - Azkya, Alya; Isfanda; Atika, Ratih Ayu (Jurnal Kedokteran Meditek, 2026)
Introduction: Staphylococcus aureus is a bacterium that causes various infections and has demonstrated increasing resistance to antibiotics, highlighting the need for alternative antibacterial agents from natural sources. The pseudostem of Musa paradisiaca var. balbisiana Colla contains flavonoids, tannins, and saponins with potential antibacterial properties. Studies evaluating the dose–response relationship of extracts from specific local sources remain limited. This study aimed to determine the effect of different concentrations of ethanolic extract of the pseudostem on the inhibition zone diameter of S. aureus. Methods: The ethanolic extract was tested at concentrations of 6.25%, 12.5%, 25%, and 50% using the disk diffusion method. Vancomycin was used as the positive control and sterile distilled water as the negative control. Data were analyzed using one-way analysis of variance with a significance level of p < 0.05, followed by a post hoc Duncan’s test. Results: The mean inhibition zone diameters were 7.48 mm, 9.18 mm, 10.12 mm, and 10.88 mm, respectively. Statistical analysis revealed significant differences among all concentrations tested. Conclusion: The extract exhibited concentration-dependent antibacterial activity and shows potential as a natural antibacterial candidate, providing novelty through dose–response analysis and supporting further research development.